SISTEM PENGUKURAN DAN OTOMATISASI DAYA LISTRIK RUMAH TANGGA MENGGUNAKAN LOGIKA FUZZY TSUKAMOTO - Siregar, Rizki Abdul Hakim; Ikhsan, Muhammad; Lubis, Aidil Halim (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: The need for an accurate household electrical power measurement and control system is becoming increasingly urgent to prevent equipment damage due to power fluctuations and to optimize energy consumption. This study tested a system with 15, 20, 25, 30, and 40-watt lamp loads using the ZMPT101B sensor for voltage and ACS712 for current, which were integrated with an Arduino Uno. Fuzzy logic was applied to control the relay based on sensor measurements, taking into account parameters such as voltage, current, and power. This fuzzy logic allows the system to make power regulation decisions automatically and adaptively in response to changes in load conditions, thereby increasing system efficiency and reliability. The results show that the system successfully achieved design and automation goals. Measurements on a 15-watt load resulted in a voltage of 218 V, a current of 0.068 A, and a power of 15.33 watts; on a 20-watt load, the voltage was 221 V, the current was 0.091 A, and the power was 19.80 watts; on a 25-watt load, the voltage was 220 V, the current was 0.114 A, and the power was 24.95 watts; on a 30-watt load, the voltage was 219 V, the current was 0.136 A, and the power was 29.84 watts; and on a 40-watt load, the voltage was 219 V, the current was 0.182 A, and the power was 40.36 watts.   Keyword: Power Measurement System, Household Energy Control, ZMPT101B Sensor, ACS712 Sensor, Arduino Uno, Fuzzy Logic Abstrak: Kebutuhan sistem pengukuran dan kontrol daya listrik rumah tangga yang akurat semakin mendesak untuk menghindari kerusakan peralatan akibat fluktuasi daya dan mengoptimalkan konsumsi energi. Penelitian ini menguji sistem dengan beban lampu 15, 20, 25, 30, dan 40watt menggunakan sensor ZMPT101B untuk tegangan dan ACS712 untuk arus, yang diintegrasikan dengan Arduino Uno. Logika fuzzy diterapkan untuk mengontrol relay berdasarkan pengukuran sensor, dengan mempertimbangkan parameter tegangan, arus, dan daya. Logika fuzzy ini memungkinkan sistem untuk membuat keputusan pengaturan daya secara otomatis dan adaptif terhadap perubahan kondisi beban, sehingga meningkatkan efisiensi dan keandalan sistem. Hasil menunjukkan bahwa sistem berhasil dalam perancangan dan otomatisasi. Pengukuran pada beban 15 watt menghasilkan tegangan 218 V, arus 0,068 A, dan daya 15,33 watt pada beban 20 watt, tegangan 221 V, arus 0.091 A, dan daya 19,80 watt pada beban 25 watt, tegangan 220 V, arus 0,114 A, dan daya 24,95 watt; pada beban 30 watt, tegangan 219 V, arus 0,136 A, dan daya 29,84 watt serta pada beban 40 watt, tegangan 219 V, arus 0,182 A, dan daya 40,36 watt.Kata kunci: Daya Listrik, Kontrol Energi Rumah Tangga, Sensor ZMPT101B, Sensor ACS712, Arduino Uno, Logika Fuzzy